PENGARUH KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP KECURANGAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023) - Luthfiyyah, Alya (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
Financial statement fraud is a high incidence of fraud compared to corruption and misuse of assets. The purpose of this research is how audit quality, audit committees and financial statement fraud are, how much influence audit quality and audit committees have on financial statement fraud, how much influence audit quality has on financial statement fraud, how much influence the audit committee has on financial statement fraud. The purpose of this study was to determine the effect of audit quality and audit committee on financial statement fraud. The data source used in the study is secondary data from the annual financial statements the study used 240 sample data from 60 companies for 4 years of research. Sampling using non-probability sampling with purposive sampling technique. To measure the effect of the sample, the classic assumption test analysis and panel data regression analysis. The condition of audit quality, audit committees and financial statement fraud in manufacturing companies in the primary consumer goods sector in the sample is in poor condition. The research results show that audit quality has a negative and significant effect on financial statement fraud. Good audit quality can reduce financial statement fraud. Furthermore, the audit committee has no effect and not significant on financial statement fraud, a poor audit committee will increase financial statement fraud. The results of simultaneous testing show that audit quality and the audit committee jointly influence financial statement fraud.